It Takes a Village: The Importance of Neuropsychological Findings in a Collaborative Approach for a Patient with Congenital Central Hypoventilation Syndrome and Specific Phobia - Sarah Hamill Skoch; Bo Fu; Amanda L. Stein; Samuel P. Greenstein (Case Reports in Psychiatry)
Congenital central hypoventilation syndrome (CCHS) is a life-threatening disorder characterized by respiratory symptoms such as hypoventilation during sleep, significantly reduced ventilatory and arousal responses, and sustained hypoxia. Patients with CCHS exhibit neurocognitive deficits due to structural abnormalities in the brainstem, cerebellum, and forebrain. Due to the potential for repeated hypoxemia and hypercarbia among patients with CCHS, neurocognitive functioning is often impaired. This is the first described report in which a patient with CCHS and specific phobia has been reported and highlights the importance of neuropsychological testing in directing treatment approaches. We report a case of a 26-year-old male, diagnosed with CCHS and specific phobia. This patient was overdue for a needed bronchoscopy to check his airway for abnormalities (recommended every 12-24 months). The patient had developed a specific phobia to procedures involving anesthesia. It was determined in the initial phase of treatment that the patient’s neurocognitive status was impacting his ability to engage in psychiatric and psychosocial treatment. This patient’s care consisted of neuropsychological testing, with medication consultation, and cognitive behavioral psychotherapy. Treatment involved consistent collaboration among the patient’s treating clinicians as well as collaboration with the patient’s family and team of nurses. At the conclusion of treatment, the patient had successfully completed his bronchoscopy and future treatment goals were identified. This case emphasizes the importance of a neuropsychological evaluation when there is a disconnect in a patient’s information processing, as the results may be highly informative in directing treatment for patients with CCHS and specific phobia. The collaborative care we provided offers insights which may direct future interventions for patients with CCHS and improve their quality of life. Our case adds support to the recommendation that patients with CCHS and impaired psychosocial functioning should receive neuropsychological testing to best direct treatment.